Benign dermatoses of the male genital areas: A review of the literature. Issue 3 (5th May 2020) - Conforti, Claudio; Giuffrida, Roberta; Di Meo, Nicola; Longone, Michela; Vichi, Silvia; Colli, Claudia; Deinlein, Teresa; Vezzoni, Roberta; Retrosi, Chiara; Errichetti, Enzo; Cannavò, Serafinella Patrizia; Zalaudek, Iris; et al.
Abstract: The male genitalia are a common site of dermatoses. Patients with penile diseases often delay or avoid medical care due to anxiety and embarrassment. In this narrative review, we describe some of the main benign dermatoses localized to male genital, focusing on their epidemiology, clinical and dermoscopic features, as well as available therapies.